Supportive people evoke positive affect, but do not reduce negative affect, while supportive groups result from favorable dyadic, not group effects. Issue 3 (4th May 2022) - Lakey, Brian; Hubbard, Sultan Ali; Woods, William C.; Brummans, Jessica; Obreiter, Amy; Fles, Elizabeth; Andrews, Justin; Vander Molen, Randy J.; Hesse, Calvin; Gildner, Brianna; Lutz, Rachel; Maley, Morgan
ABSTRACT: Background and Objectives: We addressed understudied questions in social support. Do providers, who recipients agree are more supportive than others (i.e., consensually supportive), evoke more favorable affect in recipients? Do groups differ in their supportiveness and do supportive groups evoke favorable affect in their members? Can any group differences be explained by dyadic relationships within groups? Methods: We analyzed data from seven samples of well-acquainted groups and groups of strangers in which participants rated each other on supportiveness, and affect experienced when with each group member. Results: Social Relations Model analyses indicated that consensually supportive providers evoked higher positive affect in recipients but not lower negative affect. Uniquely supportive relationships evoked higher positive and lower negative affect. Groups differed in their supportiveness and more supportive groups evoked higher positive and lower negative affect. Correlations between support and affect at the level of groups primarily reflected dyadic relationships within groups, rather than the groups themselves. Groups of strangers showed the same effects as well-acquainted groups. Conclusions: The findings for consensually supportive providers and low negative affect is inconsistent with most social support theory. Supportive groups' links to affect could be explained by dyadic relationships within groups, rather than the groups themselves.